Numerical methods for engineers : with programming and software applications - Chapra, Steven C. (WCB/McGraw-Hill, 1998)
Mathematical modeling and engineering problem-solving. Computers and software. Approximations and round-off errors. Truncation errors and the taylor series. Bracketing methods. Open methods. Roots of polynomials...